Investigation of Person Ability and Item Fit Instruments of Eco Critical Thinking Skills in Basic Science Concept Materials for Elementary Pre-Service Teachers (Jurnal Pendidikan IPA Indonesia, 2021)
The study aims to investigate Person Ability and Item Fit instruments for critical thinking skills of the environment (Eco Critical Thinking Skill) in elementary pre-service teachers. Instrument investigations were carried out by describing item fit, separation of item and person, unidimensionality, and reliability of item and person. The research method was carried out quantitatively by collecting data through an open-answer essay test and an ecocritical thinking skill test. Participants in this study were Elementary School Teacher Education (ESTE) students from 3 universities in Surabaya of East Java, Surakarta of Central Java, and Manggarai of East Nusa Tenggara. The number of participants was 110 ESTE students. Data were analyzed with the Rasch Model WINSTEP software. The result of the study is that 36% of ESTE students have high Person Ability, 58% of them have average Person Ability, and the rest (6%) have low Person Ability. Students who have higher abilities are dominated by students from campus in Surabaya at 50%. Item fit Instrument with Mean Square (MnSq) 0.7 - 1.33. ZSTD -1.4 - 2.0 and Pt-measure Corr 0.49–0.6. The research concludes that an instrument of ecocritical thinking skills is a good fit instrument. The distribution of pre-service teacher qualifications from Surakarta and Manggarai is at a medium level, and students from Surabaya-East Java dominate high ability. Elementary pre-service teachers have the most dominant ability to explain and analyze a phenomenon or fact related to environmental damage.